2019
DOI: 10.1002/anie.201905230
|View full text |Cite
|
Sign up to set email alerts
|

Diglycine Enables Rapid Intrabacterial Hydrolysis for Activating Anbiotics against Gram‐negative Bacteria

Abstract: Antimicrobial drug resistance demands novel approaches for improving the efficacy of antibiotics,especially against Gram-negative bacteria. Herein, we report that conjugating ad iglycine (GG) to an antibiotic prodrug drastically accelerates intrabacterial ester-bond hydrolysis required for activating the antibiotic. Specifically,the attachment of GG to chloramphenicol succinate (CLsu) generates CLsuGG,which exhibits about an order of magnitude higher inhibitory efficacy than CLsu against Escherichia coli. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…[ 33–35 ] For example, the conjugation of diglycine to an antibiotic prodrug is an effective strategy for accelerating enzymatic prodrug hydrolysis and enhancing the antibacterial efficacy of antibiotics. [ 36 ] The conjugation of dexamethasone and Arg‐Gly‐Asp (i.e., RGD) generates a PDC supramolecular hydrogel, which boosts the transcorneal permeability and pharmacological activity via the ligand‐receptor interaction. [ 37,38 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 33–35 ] For example, the conjugation of diglycine to an antibiotic prodrug is an effective strategy for accelerating enzymatic prodrug hydrolysis and enhancing the antibacterial efficacy of antibiotics. [ 36 ] The conjugation of dexamethasone and Arg‐Gly‐Asp (i.e., RGD) generates a PDC supramolecular hydrogel, which boosts the transcorneal permeability and pharmacological activity via the ligand‐receptor interaction. [ 37,38 ]…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] For example, the conjugation of diglycine to an antibiotic prodrug is an effective strategy for accelerating enzymatic prodrug hydrolysis and enhancing the antibacterial efficacy of antibiotics. [36] The conjugation of dexamethasone and Arg-Gly-Asp (i.e., RGD) generates a PDC supramolecular hydrogel, which boosts the transcorneal permeability and pharmacological activity via the ligand-receptor interaction. [37,38] Inspired by these studies, we integrated a polyphenol, a non-steroidal anti-inflammatory drug and a self-assembled peptide motif to generate a PDCs (2IPF-DHB-GFFYD), which could self-assemble into supramolecular hydrogel to exert the synergistic effects and consequently higher therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, compared to 23 , 25 has lower toxicity to bone marrow stromal cells, which would reduce the systemic burden. 83 This method likely would be applicable to target other enzymes, such as matrix metalloproteinases 84 and gelatinase, 85 for minimizing MDR.…”
Section: Sasms Inhibit Pathogenic Cellsmentioning
confidence: 99%
“…[39][40][41] For example, Chen et al 39 reported a guest-triggered AMP assembly system with switchable antibacterial activity. Yang et al 40 harnessed the overexpressed phosphatase in Escherichia coli to catalyze the assembly of short peptide or antibiotic-peptide conjugates, 42 activating their biological functions within the bacteria cell. Chen et al 41 developed a pH-responsive AMP nanomaterial, which could be activated only in the acidic microenvironment of the bacterial infection area.…”
Section: Introductionmentioning
confidence: 99%